An Evidence-Based Care Model for Workers With Concussion. Issue 5 (September 2019) - Thompson, Aaron; Chechulin, Yuriy; Bain, Donna; Bayley, Mark
Abstract : Objective: To evaluate the impact of an evidence-based assessment program for people with workers' compensation claims for concussion on healthcare utilization and duration of lost time from work. Setting: An assessment program for people with a work-related concussion was introduced to provide physician assessment focused on education and appropriate triage. Participants: A total of 3865 people with accepted workers' compensation claims for concussion with dates of injury between January 1, 2014, and February 28, 2017. Design: A quasiexperimental pre-/poststudy of healthcare utilization (measured by healthcare costs) and duration of time off work (measured by loss of earnings benefits) in a cohort of people with workers' compensation claims for concussion in the period prior to and following introduction of a new assessment program. Administrative data were retrospectively analyzed to compare outcomes in patients from the preassessment program implementation period to those in the postimplementation period. Results: The assessment program resulted in reduced healthcare utilization reflected by a 14.4% (95% confidence interval, −28.7% to −0.8%) decrease in healthcare costs. The greatest decrease in healthcare costs was for assessment services (−27.9%) followed by diagnostic services (−25.7%). There was no significant difference in time off work as measured by loss-of-earnings benefits. Conclusion: A care model for people with a work-related concussion involving an evidence-based assessment by a single physician focused on patient education resulted in significantly decreased healthcare utilization without increasing duration of time off work.